Studies Peningkatan Kreativitas Siswa Melalui Penerapan Model Pembelajaran Project Based Learning (PJBL) pada Mata Pelajaran PAI di Kelas VIII MTsN 1 Pasaman - Riko Pilihantoni; Muhammad Fauzan; Asmar Habibi; Agusrianto (Journal of Social, Educational and Religious Studies, 2026)
This research is motivated by the problem of low student creativity in Islamic Religious Education (PAI) learning at MTsN 1 Pasaman, characterized by teacher centered learning, the use of conventional lecture methods, and a lack of opportunities for students to actively explore. This results in low student motivation, understanding, and learning outcomes. The research aims to describe the planning, implementation, and evaluation of applying the Project Based Learning (PJBL) model to enhance student creativity in PAI subjects. The research method uses a qualitative approach with data collection techniques of observation, indepth interviews, and documentary studies. The findings indicate that the implementation of PJBL through systematic stages from theme identification, project planning, collaborative execution, to presentation and reflection successfully created active, innovative, and student-centered learning. Evaluation through self assessment, peer assessment, and product rubrics revealed a significant improvement in student creativity indicators: fluency, flexibility, originality, and elaboration of thinking. Therefore, the PJBL model is proven effective as an alternative strategy to overcome passive learning problems and enhance student creativity in the context of PAI.